Asymmetric Synthesis of Chiral Atropisomeric Bis‐Aryl Organophosphorus from Menthyl H‐Phosphinate. Issue 2 (17th March 2016) - Ma, Yan‐Na; Yang, Shang‐Dong
Abstract: This review describes new methods for the synthesis of chiral monophosphine ligands with menthyl phenylphosphinate as a chiral auxiliary through asymmetric Suzuki‐Miyaura cross‐coupling reactions and asymmetric C–H functionalization. The chiral menthyl phenylphosphinate as a chiral auxiliary is easy to prepare and the menthyl group can easily be transformed into other functional groups, with the chiral center synchronously remaining. These methodologies provide highly efficient and practical strategies for the synthesis of novel axially chiral biaryl monophosphine oxides and their corresponding phosphines. Meanwhile, these reactions are easy to handle and exhibit wide scope for substrates with excellent diastereomeric ratios. Abstract : Asymmetric synthesis of chiral atropisomeric bis‐aryl organophosphorus from menthyl H‐phosphinate : new methods for the synthesis of chiral monophosphine ligands with menthyl phenylphosphinate as a chiral auxiliary through asymmetric Suzuki‐Miyaura cross‐coupling reactions and asymmetric C–H functionalization are described.